The influence of principal leadership and the availability of facilities and infrastructure on teacher performance - Indah, Sandra Gamba; Sulastri, Sulastri; Syahril, Syahril; Rifma, Rifma (Universitas Jambi, Indonesia, 2026)
This study explores the influence of principal leadership and the availability of facilities and infrastructure on teacher performance in MTS Negeri Padang Lawas Regency. Using a quantitative correlational approach, the research examines how principal leadership and resources contribute to enhancing teacher performance. Data were collected through a questionnaire administered to 56 teachers, with results analyzed using descriptive statistics, normality tests, homogeneity tests, multicollinearity tests, and linearity tests. The findings reveal that principal leadership accounts for 18% of teacher performance variation, while the availability of facilities and infrastructure contributes 22.2%. Together, these two factors explain 37.8% of the variation in teacher performance. The study emphasizes the importance of improving both leadership skills and educational resources to enhance teaching effectiveness. These results suggest that investment in leadership development and school infrastructure should be prioritized to achieve better educational outcomes.